2012
DOI: 10.1103/physrevb.85.235201
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast optical studies of ordered poly(3-thienylene-vinylene) films

Abstract: Using femtosecond transient photomodulation, photoluminescence, and electro-absorption spectroscopies, we studied the ultrafast photoexcitation dynamics and nonlinear optical properties of ordered poly(thienylenevinylene) (PTV), which belongs to a rare class of nonluminescent, nondegenerate-ground-state π-conjugated polymers. We show that the ordered PTV films contain abundant nanocrystalline domains that substantially influence the optical spectra as a result of aggregates formation. We demonstrate that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
4
29
0
Order By: Relevance
“…These may potentially be related to the coherent phonon oscillations within the Ag mirror, 63 but we additionally note that photoexcitation has been reported to create localized strain in thin films, resulting in propagating strain waves that manifest as time-domain oscillations in the transmission signal. [81][82][83][84] These effects can be difficult to detect when superimposed with bulk electronic signatures. However, in a metallic BODIPY-R microcavity we can well describe the principal decay dynamics of the prominent transient bands with a global multi-exponential fit, and the residual shows evidence for a weak, slowly oscillating component (Figure 4b-d).…”
Section: Resultsmentioning
confidence: 99%
“…These may potentially be related to the coherent phonon oscillations within the Ag mirror, 63 but we additionally note that photoexcitation has been reported to create localized strain in thin films, resulting in propagating strain waves that manifest as time-domain oscillations in the transmission signal. [81][82][83][84] These effects can be difficult to detect when superimposed with bulk electronic signatures. However, in a metallic BODIPY-R microcavity we can well describe the principal decay dynamics of the prominent transient bands with a global multi-exponential fit, and the residual shows evidence for a weak, slowly oscillating component (Figure 4b-d).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we investigate the roles of mode-specific vibrational displacements on triplet formation dynamics in an alkyl-substituted trans -thienylene–vinylene dimer (dTV; see Scheme ), a small-molecule analogue of poly­(thienylene–vinylenes) (PTV). PTV photophysics, though well studied, have remained controversial largely due to the short-lived nature of their excited states. For example, dipole-forbidden midgap excited states (i.e., 2A g ) have been invoked to explain rapid excited-state relaxation and nonemissive behavior commonly observed in these systems. ,, This model was next amended by Musser et al to include a singlet fission process within ∼45 fs followed by relaxation of the triplet pair to the 2A g state and subsequent decay to the ground electronic state . However, Hu et al demonstrated that fluorescence emission could be restored by dispersing a PTV derivative in a solid inert host, causing aggregates to dissociate .…”
mentioning
confidence: 99%
“…12−14 For example, dipoleforbidden midgap excited states (i.e., 2A g ) have been invoked to explain rapid excited-state relaxation and nonemissive behavior commonly observed in these systems. 12,15,16 This model was next amended by Musser et al to include a singlet fission process within ∼45 fs followed by relaxation of the triplet pair to the 2A g state and subsequent decay to the ground electronic state. 14 However, Hu et al demonstrated that fluorescence emission could be restored by dispersing a PTV derivative in a solid inert host, causing aggregates to dissociate.…”
mentioning
confidence: 99%
“…28−30 Despite morphology controllability issues, 31 PTVs caused by ultrafast nonradiative decay have been ascribed as the main causes for low OSC performance. 32 Thus, in order for PTVs to be more applicable for OSCs and other optoelectronic applications in general, systematic structural modifications, especially those that perturb the main-chain electronic structures, optimization in physical/electronic properties and, most importantly, better understanding on structure−property relationships are necessary. All of these aspects have been explored to a very limited extent mainly due to the limitations in PTV structural variations by conventional synthetic procedures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Structural variations in these PTVs are simply alterations of alkyl chain lengths and topologies (linear vs branched), resulting in similar electronic properties among the existing examples. Applications of these soluble PTVs in organic electronic devices have been scarce, among which several examples of applying PTVs in OSCs have been described but only low to moderate device efficiencies, typically less than 1%, have been obtained. Despite morphology controllability issues, extremely short exciton lifetimes in PTVs caused by ultrafast nonradiative decay have been ascribed as the main causes for low OSC performance . Thus, in order for PTVs to be more applicable for OSCs and other optoelectronic applications in general, systematic structural modifications, especially those that perturb the main-chain electronic structures, optimization in physical/electronic properties and, most importantly, better understanding on structure–property relationships are necessary.…”
Section: Introductionmentioning
confidence: 99%